1964
DOI: 10.1113/expphysiol.1964.sp001696
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholine Metabolism in Salivary Glands During the “Degeneration Secretion”

Abstract: The synthesis and breakdown of ACh have been studied in the submaxillary gland of the cat and in the parotid gland of the rabbit during the "degeneration secretion", that is during the first days after postganglionic parasympathetic denervation.The decrease in the cholinesterase activity found in both glands cannot be the cause of the secretory activity. It might, however, increase and prolong the secretion in the rabbit's parotid gland.The "degeneration secretion" and the disappearance of choline acetylase ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
8
0

Year Published

1965
1965
1983
1983

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 11 publications
2
8
0
Order By: Relevance
“…The finding that the ACh-synthesis of rat submaxillary glands increased after sympathetic ganglionectomy indicated that there was a growth of cholinergic neurones after this type of denervation [Nordenfelt, 1964 a]. In the present investigation it is shown that the ChE activities also increase significantly and that the rise is of about the same order as the ChAc increase after sympathetic denervation.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The finding that the ACh-synthesis of rat submaxillary glands increased after sympathetic ganglionectomy indicated that there was a growth of cholinergic neurones after this type of denervation [Nordenfelt, 1964 a]. In the present investigation it is shown that the ChE activities also increase significantly and that the rise is of about the same order as the ChAc increase after sympathetic denervation.…”
Section: Discussionsupporting
confidence: 66%
“…When investigations were made in other species it was not possible to demonstrate a change of the ChAc activity after postganglionic sympathetic denervation in salivary glands of the rabbit and dog, but in the submaxillary gland of the rat a ChAc increase was clearly shown [Nordenfelt, 1964 a], which was also verified by Ohlin and Perec [1967].…”
mentioning
confidence: 73%
“…The main cause, however, is that the leakage of acetylcholine from the post-ganglionic nerve endings which occurs normally but in quantities too small to evoke secretion (Emmelin, 1960(Emmelin, , 1965Assarson & Emmelin, 1964), temporarily increases above the secretory threshold. At one stage of degeneration the nerve endings can still synthesize acetylcholine (Nordenfelt, 1964) (Weiss & Hiscoe, 1948;Weiss, 1961Weiss, , 1963 has been supposed to be concerned with at least some of the components engaged in the transmission procedure at the endings, acetyleholinesterase and choline acetyltransferase (Feldberg & Vogt, 1948;Sawyer, 1946;Hebb & Waites, 1956;Lubinska, Niemierko & Oderfeld, 1961;Hebb & Silver, 1961;Lubinska, Niemierko & Zelena', 1963). It is also known that denervation supersensitivity, assumed to be due to loss of an action ofacetylcholine, appears earlier (Luco & Eyzaguirre, 1955;Emmelin & Malm, 1965) and that the ability to synthesize acetylcholine decreases earlier (Emmelin, Nordenfelt & Perec, 1966) the nearer the effector a cholinergic nerve has been cut.…”
mentioning
confidence: 99%
“…Mott (1965) One or two days after post-ganglionic parasympathetic denervation saliva was found to flow from the parotid, submaxillary, and sublingual glands of anaesthetized cats. This 'degeneration secretion' was attributed to acetylcholine release from the nerve endings (Emmelin and Stromblad, 1958;Emmelin, 1962), which at a certain stage of degeneration still can synthesize acetylcholine but seem unable to retain it in a normal way (Nordenfelt, 1964). In the present experiments the early period of the 'degeneration secretion' was studied in parotid glands of cats.…”
Section: P Physiological Society 4-5 November 1966 43pmentioning
confidence: 99%